Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

7x - 4y = 5 and 8x + y = -11

Transform one equation into its Slope-intercept form (y=mx+b)

8x + y = -11

y = -8x - 11

Substitute the value of "y" (-8x - 11) as the value of "y" to the other equation.

7x - 4 (-8x - 11) = 5

7x + 32x + 44 = 5

39x + 44 = 5

39x = 5 - 44

39x = -39

x = -1

Substitute the value of "x" (-1) as the value of "x" to the other equation.

8(-1) + y = -11

-8 + y = -11

y = -11 + 8

y = -3

Solutions: (-1,-3)

-KookEin

Transform one equation into its Slope-intercept form (y=mx+b)

8x + y = -11

y = -8x - 11

Substitute the value of "y" (-8x - 11) as the value of "y" to the other equation.

7x - 4 (-8x - 11) = 5

7x + 32x + 44 = 5

39x + 44 = 5

39x = 5 - 44

39x = -39

__39x__=__-39__

39 39x = -1

Substitute the value of "x" (-1) as the value of "x" to the other equation.

8(-1) + y = -11

-8 + y = -11

y = -11 + 8

y = -3

Solutions: (-1,-3)

-KookEin